Multifunctional single beam acoustic tweezer for non-invasive cell/organism manipulation and tissue imaging - Lam, Kwok Ho (Sci Rep, 2016)
Non-contact precise manipulation of single microparticles, cells, and organisms has attracted considerable interest in biophysics and biomedical engineering. Similar to optical tweezers, acoustic tweezers have been proposed to be capable of manipulating microparticles and even cells. Although there have been concerted efforts to develop tools for non-contact manipulation, no alternative to complex, unifunctional tweezer has yet been found. Here we report a simple, low-cost, multifunctional single beam acoustic tweezer (SBAT) that is capable of manipulating an individual micrometer scale non-spherical cell at Rayleigh regime and even a single millimeter scale organism at Mie regime, and imaging tissue as well. We experimentally demonstrate that the SBAT with an ultralow f-number (f# = focal length/aperture size) could manipulate an individual red blood cell and a single 1.6 mm-diameter fertilized Zebrafish egg, respectively. Besides, in vitro rat aorta images were collected successfully at dynamic foci in which the lumen and the outer surface of the aorta could be clearly seen. With the ultralow f-number, the SBAT offers the combination of large acoustic radiation force and narrow beam width, leading to strong trapping and high-resolution imaging capabilities. These attributes enable the feasibility of using a single acoustic device to perform non-invasive multi-functions simultaneously for biomedical and biophysical applications.